Efficacy of NEPA, a fixed antiemetic combination of netupitant and palonosetron, vs a 3‐day aprepitant regimen for prevention of chemotherapy‐induced nausea and vomiting (CINV) in Chinese patients receiving highly emetogenic chemotherapy (HEC) in a randomized Phase 3 study. (30th May 2020) - Chang, Jianhua; Chen, Gongyan; Wang, Dong; Wang, Guihua; Lu, Shun; Feng, Jifeng; Li, Wei; Li, Ping; Lanzarotti, Corinna; Chessari, Salvatore; Zhang, Li
Abstract: NEPA is the only fixed combination antiemetic, comprised of an NK1 RA (netupitant) and a 5‐HT3 RA (palonosetron). In the first head‐to‐head trial to compare NK1 RA‐containing regimens, a single oral dose of NEPA was non‐inferior to a 3‐day aprepitant/granisetron (APR/GRAN) regimen for the primary endpoint of overall (0‐120 hours) complete response (no emesis/no rescue). This pre‐specified analysis evaluates the efficacy of NEPA versus APR/GRAN in the subset of Chinese patients in the study. In addition, efficacy in patients at greatest emetic risk receiving high‐dose cisplatin (≥70 mg/m 2 ) was explored. Chemotherapy‐naïve patients with solid tumors in this randomized, double‐blind study received either a single dose of NEPA prior to cisplatin‐based chemotherapy or a 3‐day regimen of APR/GRAN, both with dexamethasone on Days 1‐4. Efficacy was evaluated through complete response, no emesis, and no significant nausea rates during the acute (0‐24 hours), delayed (25‐120 hours) and overall phases as well as individual days post‐chemotherapy, as the daily course of CINV protection is often unstudied. The Chinese subset included 667 patients; of these, 363 (54%) received high‐dose cisplatin. Baseline characteristics were comparable. While response rates were similar for NEPA and APR/GRAN during the acute, delayed and overall phases, significantly fewer NEPA patients experienced breakthrough CINV on individual Days 3‐5 in both the Chinese patients and also in those receiving high‐dose cisplatin. As a fixed oral NK1 RA/5HT3 RA combination given once/cycle, NEPA is a convenient highly effective prophylactic antiemetic that may offer better protection from CINV than a 3‐day APR/GRAN regimen on Days 3‐5 following highly emetogenic chemotherapy. Abstract : NEPA is a novel fixed combination antiemetic comprised of the NK1 RA, netupitant, and the 5‐HT3 RA, palonosetron. The simultaneous targeting of two critical antiemetic pathways, in unison with single‐dose administration, offers a simplified and convenient antiemetic with 5‐day CINV prevention. The authors report significantly better protection from CINV during Days 3‐5 post‐chemotherapy for NEPA vs a 3‐day regimen of aprepitant/granisetron in Chinese patients, and in those receiving high‐dose cisplatin, in the first head‐to‐head study comparing NK1 RA‐containing regimens.